Trends in Antibiotic Resistance Among Bacterial Isolates from Diverse Water Samples Across Dhaka city, Bangladesh - Himi, Humayra Zaman; Ivy, Sanjida Chowdhury; Begum, Samsunnahar; Bhuiyan, Mohiuddin Ahmed; Islam, Md Rabiul; Dewan, Syed Masudur Rahman; Shahriar, Mohammad (Dhaka University Journal of Pharmaceutical Sciences, 2025)
The study aimed to explore whether there is any relationship between microbial contamination and its resistance ratio in drinking water samples of Dhaka city. This study will provide insights into the state of water processing in Dhaka, offering a comprehensive view of the situation. A prospective prevalence study was done on different water samples from different locations in Dhaka, Bangladesh. The study involved collecting fifty samples from July to December 2023. All isolates were identified using bacterial culture and a panel of biochemical tests. For each identified isolate, antibiogram profiles were established using the agar diffusion test following the Clinical and Laboratory Standards Institute (CLSI) guidelines. 50 specimens were grown. Among the isolates, gram-positive and gram-negative were 47.80% and 52.20%, respectively. The distribution of these bacteria in different water sources varied significantly based on the research results. Notable gram-negative bacteria like E. coli, Enterobacter sp., Salmonella paratyphii, Vibrio cholerae, and Shigella sp. were identified in the sources. Jar water from street vendors displayed a comparable distribution, with a greater incidence of gram-negative bacteria at 53.85% versus gram-positive bacteria at 46.15%. Pseudomonas aeruginosa, Salmonella typhii, Salmonella paratyphii, and Shigella sp. were dominant among gram-negative isolates, while Staphylococcus sp., S. aureus, and S. epidermidis were the leading gram-positive contaminants. Filtered water from electronic sources showed a slight shift, with more gram-positive bacteria at 53.57% and dominant isolates like Micrococcus sp., S. aureus, and Streptococcus sp. Klebsiella pneumoniae being the primary gram-negative bacteria in this category. In the jar water from other sources, gram-negative bacteria accounted for 51.72% of isolates, with Klebsiella sp., Proteus mirabilis, and Pseudomonas aeruginosa as the main contaminants, while gram-positive bacteria like S. epidermidis and Micrococcus sp. were also present. These findings highlight the diverse bacterial isolates that showed resistance to azithromycin, ceftriaxone, aztreonam, nalidixic acid and cefepime. In this study, the isolation of pathogenic bacteria from drinking water indicates that they can be vehicles for disease transmission. The finding of the study indicates a rising trend in antimicrobial resistance among bacterial isolates over time. To combat rising antimicrobial resistance, policymakers and water authorities must adopt a proactive, multi-pronged approach. This includes increasing surveillance,updating water treatment, encouraging ethical antibiotic use, funding research, creating public awareness and promoting international cooperation. These concerted activities are critical for slowing the spread of resistance while protecting public health and the environment. Dhaka Univ. J. Pharm. Sci. 24(2): 121-130, 2025 (December)